2015
DOI: 10.1063/1.4939031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the biocompatibility of three-dimensional-printed polymers using multispecies toxicity tests

Abstract: Additive manufacturing was adopted in multiple fields of life sciences. It is also becoming a popular tool for rapid prototyping of microfluidic and biomedical devices. Limited studies have been performed to investigate the biological implications of using 3D printed polymers. Here we assessed the biocompatibility of seven commercially available polymers, using a battery of standardized bioassays for chemical risk assessment. Our data show that leachates from photopolymers substrata appear to be very toxic to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
1
53
0
1
Order By: Relevance
“…WaterShed becomes yellow under prolonged exposure to ambient light 10 . Moreover, a recent systematic investigation has shown that many of the popular 3D-printing resins (including Visijet Crystal or WaterShed) release toxic leachates that inhibit growth of cells from different vertebrate and invertebrate indicator organisms 19 . Zebrafish embryos cultured on these resins showed developmental defects 20 .…”
Section: Introductionmentioning
confidence: 99%
“…WaterShed becomes yellow under prolonged exposure to ambient light 10 . Moreover, a recent systematic investigation has shown that many of the popular 3D-printing resins (including Visijet Crystal or WaterShed) release toxic leachates that inhibit growth of cells from different vertebrate and invertebrate indicator organisms 19 . Zebrafish embryos cultured on these resins showed developmental defects 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Although 'Rx' Visijet Crystal recorded almost 100% survival rates in Test 1 and Test 2, tests were concluded on day 2 due to the severity of sublethal and teratogenic effects observed in embryos. Previous studies 8,10) have also reported Visijet materials to be unsafe in zebrafish assays. Although it is not unusual for zebrafish under 120 hpf to spend most of their time lying inactively on the bottom of the tanks until the inflation of their swim bladder 24) , those exposed to AM materials showed increased lethargy or behavioural perturbations, which often precede mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the AM-produced devices may consequently vary when identical parts are built using different 3D printers or even when the same 3D printer, parameters, process steps, and materials are used 2) . An issue of concern is recent studies highlighting their potential toxicity [8][9][10][11] . By being toxic, there is a relative ability of the materials to cause injury to biological tissues, ranging from improper biochemical function, organ damage, and cell destruction, to death 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous extracts from all SL polymers induced 100% mortality of Daphnia sp. neonates after 24 hours, and all SL and MJM polymers proved to be significantly toxic to zebrafish embryos 112 (Figure 9D). Zebrafish embryos cultured in 3D-printed structures made of Visijet Crystal or Watershed showed developmental defects 112,113 , whereas those grown in leachate extracts of ABS and PLA did not have any behavioral abnormalities 112 .…”
Section: Transition From Soft Lithography To 3d-printingmentioning
confidence: 99%
“…A couple of recent studies presented a comprehensive toxicity profiling of the leachates of some commercially available resins and polymers that are commonly used in 3D printing – ABS (FDM), PLA (FDM), VisiJet Crystal (MJM), Visijet SL Clear (MJM), Watershed 11122 XC (SL), Dreve Fototec 7150 Clear (SL), Form 1 Clear (SL) 112,113 . Zhu et al observed significant growth inhibition in freshwater microalgae when they were cultured for 48-96 hours in water-soluble leachate extracted from all 3D-printed structures 112 . Aqueous extracts from all SL polymers induced 100% mortality of Daphnia sp.…”
Section: Transition From Soft Lithography To 3d-printingmentioning
confidence: 99%